Risk factors for nasal septal perforation after septoplasty operation - Yıldız, Erkan; Ulu, Şahin; Kahveci, Orhan Kemal (Journal of Surgery and Medicine, 2019)
Aim: Nasal septal perforation is the most common complication in the long term after septoplasty. Nasal septal perforation is the partial opening of the wall between both nasal cavities. In this study, we will evaluate the causes of septal perforation after septoplasty. Methods: 400 patients aged between 18 and 50 years who underwent septoplasty operation in Otorhinolaryngology clinic between 2016 and 2019 were evaluated. The study was performed as a retrospective cohort. These patients were divided into groups with and without perforation. Patients with perforation were evaluated in terms of age, gender, alcohol and cigarette use, and stabilization technique used in surgery. Results: There were 280 male and 120 female patients in the study. 378 patients had no postoperative septal perforation. 22 had perforation after surgery. 19 of the patients in the perforated group were male and 3 were female. Male sex ratio was significantly dominant in perforated patients (19/3) (P=0.022). 21 of the patients were smoking and 1 patient was not drinking. (P=0.012). 11 of these patients were drinking alcohol and 10 of them did not drink alcohol. To stabilize the septum in patients with perforation while transseptal suturation + nasal splint was used in 14 patients, only nasal splint was used in 8 patients. The perforation rate after surgery was 22/400 (1.3%) (21/1) (P=0.012). There was no significant difference in the perforation rate among the patients with alcohol intake (P=0.082). There was significant difference between the methods used to stabilize the septum. The rate of perforation was significantly increased in patients who underwent transseptal suturation (P=0.023). Conclusion: Patients with perforation after septoplasty were found to increase the risk of perforation by male sex, smoking and surgical technique as transseptal suturing technique.